2003
DOI: 10.1126/science.1078546
|View full text |Cite
|
Sign up to set email alerts
|

COMT val 158 met Genotype Affects µ-Opioid Neurotransmitter Responses to a Pain Stressor

Abstract: Responses to pain and other stressors are regulated by interactions between multiple brain areas and neurochemical systems. We examined the influence of a common functional genetic polymorphism affecting the metabolism of catecholamines on the modulation of responses to sustained pain in humans. Individuals homozygous for the met158 allele of the catechol-O-methyltransferase (COMT) polymorphism (val158met) showed diminished regional mu-opioid system responses to pain compared with heterozygotes. These effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
673
9
40

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 1,028 publications
(755 citation statements)
references
References 36 publications
33
673
9
40
Order By: Relevance
“…Previously, individuals with the COMT Val/Val genotype have been found to be less susceptible to pain [4], and in one study migraine was less frequent among those with the Val/Val genotype [5]. In contrast, the distribution of the Val/Val genotype and other genotypes were similar between controls and migraine patients in the present study.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Previously, individuals with the COMT Val/Val genotype have been found to be less susceptible to pain [4], and in one study migraine was less frequent among those with the Val/Val genotype [5]. In contrast, the distribution of the Val/Val genotype and other genotypes were similar between controls and migraine patients in the present study.…”
Section: Discussioncontrasting
confidence: 45%
“…Individuals with the Val/Val genotype have a three-to fourfold higher activity of the COMT enzyme than those with Met/Met genotype [3]. Individuals with the Val/Val genotype have been found to be less susceptible to pain and to have an enhanced opioid system response to pain compared with those with other genotypes [4]. In accordance with this result, two case-control studies have found that migraine and fibromyalgia were less frequent among those with the Val/Val genotype [5,6].…”
mentioning
confidence: 99%
“…7,8 While carriers of the Val 158 allele showed a small but significant increase in perseverative errors in an executive function task [9][10][11] and reduced working memory function, 12 recent findings indicate that a compensating advantage of the Val 158 allele may be an increase in emotional resilience against anxiety, affective disorders and sustained pain. [13][14][15][16][17][18] Behavioral genetics has revealed an effect of the COMT Val 158 Met genotype 4 on negative mood states 17,19 and on another intermediate phenotype, executive cognitive function. 9 A functional 20,21 22-23-bp imperfect repeat polymorphism in the regulatory region (5-HTTLPR) of the serotonin transporter gene (SCL6A4) creates a short (S) allele and a long (L) allele (14-and 16-repeat alleles) and alters promoter activity.…”
Section: Introductionmentioning
confidence: 99%
“…37,39 The number of low-activity COMT-Met 158 alleles was positively correlated with brain activation elicited by aversive stimuli in the left hippocampus and the right amygdala 38 and predicted opioid system activations in the amygdala and elsewhere after painful stimuli. 17 Therefore, we tested the hypothesis that processing of unpleasant stimuli in the limbic system is increased with low expression of 5-HTT, that is, higher number of S and G alleles of 5-HTTLPR and rs25531, respectively, as well as with low COMT activity, that is, the dose of met 158 alleles. As 5-HTT and COMT activity should independently affect 5-HT, DA and NE levels, we hypothesized additive effects of genotypes (i.e., no significant interactions).…”
Section: Introductionmentioning
confidence: 99%
“…They are fundamentally, multiply intertwined. For example, which variant a child has of the COMT gene (the gene that codes for the COMT enzyme, important for clearing dopamine from extracellular space in prefrontal cortex [47]) can affect that child's cognitive functioning [48] and reactivity to stress [49]. Analyses of genes, such as the COMT gene, that affect neurotransmitter systems, provide a window into neurochemical modulation of cognitive and affective function.…”
Section: Learning Across Developmentmentioning
confidence: 99%